Controls on Cyclic Formation of Quaternary Early Diagenetic Dolomite - J. McCormack; T. R. R. Bontognali; A. Immenhauser; O. Kwiecien (Geophysical Research Letters)
Abstract The origin of sedimentary dolomite and the factors that control its formation within the geological record remain speculative. In most models, dolomite formation is linked to evaporative conditions, high water temperature, increasing Mg/Ca ratio, increasing alkalinity, and high amounts of biomass. Here we challenge these archetypal views, by documenting a case example of Quaternary dolomite which formed in Lake Van at constantly low temperature (<4°C) and without direct control of the latter conditions. Dolomite occurs within highstand sediments related to suborbital climate variability (Dansgaard‐Oeschger cycles). We propose that dolomite precipitation is a product of a microbially influenced process, triggered by ecological stress, resulting from reventilation of the water‐sediment interface. Independently from the validity of this hypothesis, our results call for a reevaluation of the paleoenvironmental conditions often invoked for early diagenetic dolomite‐rich intervals within sedimentary sequences and for caution when interpreting time series of subrecent lacustrine carbonates.